2004
DOI: 10.1038/sj.npp.1300399
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Volume Reductions in Pediatric Patients with Obsessive–Compulsive Disorder Treated with Paroxetine: Preliminary Findings

Abstract: The amygdala is believed to be highly relevant to the pathophysiology of obsessive-compulsive disorder (OCD) given its prominent role in fear conditioning and because it is an important target of the serotonin reuptake inhibitors (SRIs), the pharmacotherapy of choice for OCD. In the present study, we measured in vivo volumetric changes in the amygdala in pediatric patients with OCD following 16 weeks of monotherapy with the selective SRI, paroxetine hydrochloride. Amygdala volumes were computed from contiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 57 publications
4
68
0
2
Order By: Relevance
“…In a study on 23 pediatric patients with a diagnosis of OCD but with no previous treatment, a smaller volume of the globus pallidus and a greater volume of the anterior cingulate cortex were detected compared to 26 healthy controls using semi-automated, ROI-based methods. 56 A greater volume of the pituitary gland was also detected using the manual ROI method in untreated pediatric patients with OCD, being more prominent among boys. 57 A recent study using the ROIbased approach on a sample of never-medicated adults detected a reduced volume of the right and left orbitofrontal cortex and a greater volume of the thalamus, also bilaterally.…”
Section: -52mentioning
confidence: 85%
See 1 more Smart Citation
“…In a study on 23 pediatric patients with a diagnosis of OCD but with no previous treatment, a smaller volume of the globus pallidus and a greater volume of the anterior cingulate cortex were detected compared to 26 healthy controls using semi-automated, ROI-based methods. 56 A greater volume of the pituitary gland was also detected using the manual ROI method in untreated pediatric patients with OCD, being more prominent among boys. 57 A recent study using the ROIbased approach on a sample of never-medicated adults detected a reduced volume of the right and left orbitofrontal cortex and a greater volume of the thalamus, also bilaterally.…”
Section: -52mentioning
confidence: 85%
“…59 Serotoninergic transmission in this brain area has been associated with the modulation of fear and of conditioned anxiety, factors that seem to play an important role in OCD. 59 Other limbic structures have been evaluated in the various morphometric MRI studies of OCD, having been detected inconsistencies in volumetric changes, such as an increase 56 and a reduction of the cingulate cortex, 54,60 an increase of the temporolimbic cortex and of the insula, 54 and a reduction of the insulo-opercular region. 53 Reduction of the white and gray matter in the right parietal cortex was also found, 54,60 an area not previously investigated in structural studies by ROI, but which had already shown lower activity in studies of functional neuroimaging.…”
Section: -52mentioning
confidence: 99%
“…Abnormalities in the regions of hippocampus and amygdala have been emphasized in studies involving positron emission tomography (PET) or functional magnetic resonance imaging (fMRI), and researchers have commented that these regions may play an important role in the pathophysiology of OCD, with neglected discussion [27,28] . Moreover, in OCD, there is a loss of normal hemispheric asymmetry of the hippocampus-amygdala complex [16] and differences in amygdala volumes [29] .…”
Section: Hippocampus-amygdala Complexmentioning
confidence: 99%
“…On the University of Pittsburgh MR scanner a three dimensional SPGR acquisition in the steady state pulse sequence was utilized to obtain 1.5 mm coronal images (TE = 20 msec, TR = 40 msec, acquisition matrix = 256 x 192, FOV = 20 cm, flip angle = 10°). Image acquisition has been described in detail in our previous reports (Gilbert et al, 2000, MacMaster and Kusumakar, 2004a, MacMaster and Kusumakar, 2004b, MacMaster et al, 2006, Nolan et al, 2002, Rosenberg et al, 1997, Szeszko et al, 2004a, Szeszko et al, 2004b. All MRI scans were reviewed to rule out any clinically significant abnormalities.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%